PEMBUATAN SPANDUK INFOGRAFIS GUNA MENINGKATKAN TRANSPARANSI DAN EFEKTIVITAS PELAYANAN PENERBITAN SKTM DI KANTOR DESA OGOTUA KABUPATEN TOLITOLI - Moh. Wahyu; Amanda Octaviani; Mohammad Sawir; Ramdan Yusuf (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve the transparency and effectiveness of issuing the Certificate of Indigency (SKTM) in Ogotua Village through the provision of service flow infographics. The background of this activity lies in the limited public understanding of administrative procedures, which often leads to mistakes in submitting documents. The method consisted of planning, observation, infographic design using Canva, printing, frame construction, and the official handover to village officials. The results show that the infographic displayed in the village office successfully provided clear and accessible information for the community, while also demonstrating the local government's commitment to transparent public services. Through this visual medium, residents can more easily follow the SKTM issuance procedure in an orderly and compliant manner